Sequential islet transplants for type 1 diabetes are not associated with sustained or cumulative increases in hepatic portal venous pressure - Alice L. J. Carr; Rahi Shah; Braulio A. Marfil-Garza; Anna Lam; Khaled Dajani; Blaire Anderson; Richard T. J. Owen; Doug O’Gorman; Tatsuya Kin; David Bigam; A. M. James Shapiro; Peter A. Senior (PLoS ONE, 2025)
Islet transplantation (ITx) is advancing rapidly, with clinical trials of stem cell derived islets demonstrating short-term insulin independence. However, long-term insulin independence may still require multiple infusions. We examined the effects of sequential ITx on portal venous pressure and factors influencing acute pressure changes across 693 intraportal ITx procedures in 298 adults (44% M); who received up to 5 procedures, at the University of Alberta Hospital over 24 years. We assessed acute portal pressure changes per infusion, using linear mixed-effects models to compare sequential pre-infusion pressures to baseline and assess relationships between pressure changes and packed cell volume (PCV), purity, islet dose (IE/kg) and estimated total liver volume (eTLV). Portal pressure transiently increased, similarly, after each infusion by an overall median 2.0 mmHg (IQR 1.0,4.0). PCV exhibited the strongest relationship with change in pressure, with1mmHg increase per 1 mL of PCV, when adjusted for other parameters (Coefficient = 1.0 [95%CI 0.81,1.21];p < 0.0001). Conversely, higher purity and larger eTLV were associated with smaller increases in pressure. A significant interaction term indicated that the effect that PCV has on pressure change may be moderated at higher purities. Our work provides insights from deceased-donor intraportal ITx that can inform the design of future clinical protocols for ITx.